A Novel Gripper design for Diaphragm spring plate Pick and Place Cobot - Jaison, Jerry; Nagaraj, Vasudevan; Selvakumar A, Arockia (International Journal of Engineering and Technology, 2018)
Robot integrated manufacturing has turned out to be the future of manufacturing automation technology.Â Worker assisting robots perform simultaneously operation including machining, assembly, inspection, material handling etc. and in some case multiple operations in the same system at a faster and precise rate. Collaborative robots are human and computer controlled hybrid material handling device which facilitates the concept of shared workspace. To exploit its function, gripper mechanisms are inevitable. This project focuses on the design of cobotic grippers for pick and place application. Of the different concepts compared a suitable design is chosen. The gripper moves according to the signals received from the cobot, sensors and PLC control system.Â Â